Evaluasi Strategi Bersaing di TK Tunas Kasih Klungkung - Marsye Ruth Hendria Pasanea; Ade Iriani; Wasitohadi Wasitohadi (Kelola: Jurnal Manajemen Pendidikan, 2022)
The study aims to evaluate the Competitive Strategy in Tunas Kasih Klungkung Kindergarten. Evaluation is carried out based on Consistency, Suitability, Superiority, and Appropriateness. The subjects in this study were principals, teachers, and parents of students. The type of research used is descriptive, evaluative research with an interview, observation, and document study techniques. Data analysis is used Miles & Huberman's technique with the stages of data collection, data presentation, and conclusion. Data validation uses the triangulation technique and sources. The results showed: (1) in the evaluation of consistency, superior strategy programs (art performance, family gatherings, additional lessons, sharing time) that were made were still consistent with the goals and visions, missions, and also the school’s motto., (2) In the evaluation of usability, superior programs at Tunas Kasih Klungkung Kindergarten are made and adapted to the conditions, need of parents, students, and culture Public., (3) In the evaluation of excellence, superior programs at Tunas Kasih Klungkung Kindergarten can be said to be still superior, this is because the superior program that has run by the school more on the motto of Love. Apart from that, in terms of quantity, there are still many devotees, although not as much as the previous year., (4) In feasibility evaluation, the flagship program at Tunas Kasih Klungkung Kindergarten can still be said to be feasible to remain in use, this is because of the availability of infrastructure facilities and also facilities and teachers who are ready in carrying out excellent program activities. However, facilities still use outside assistance. It is hoped that in the future the school will develop these facilities to support your activities more effectively.